ChemInform Abstract: Covalent or Supramolecular Combinations of Resorcinarenes and Porphyrinoids. Issue 43 (7th October 2016) - Dumoulin, Fabienne; Topkaya, Derya; Yasar, Songuel; Ahsen, Vefa; Isci, Uemit
Abstract: Review: 39 refs.